MKK3/6-p38 MAPK negatively regulates murine MMP-13 gene expression induced by IL-1 beta and TNF-alpha in immortalized periodontal ligament fibroblasts - Rossa, C.; Liu, M.; Patil, C.; Kirkwood, K. L. (Elsevier B.V., 2005)
Matrix metalloprotease-13 (MMP-13) or collagenase-3 is involved in a number of pathologic processes such as tumor metastasis and angiogenesis, osteoarthritis, rheumatoid arthritis and periodontal diseases. These conditions are associated with extensive degradation of both connective tissue and bone. This report examines gene regulation mechanisms and signal transduction pathways involved in Mmp-13 expression induced by proinflammatory cytokines in periodontal ligament (PDL) fibroblasts. Mmp-13 mRNA expression was increased 10.7 and 9.5 fold after stimulation with IL-1 beta (5 ng/mL) and TNF-alpha (10 ng/mL), respectively. However, inhibition of p38 MAPKinase with SB203580 resulted in significant (p < 0.001) induction (23.2 and 18.1 fold, respectively) of Mmp-13 mRNA as assessed by real time PCR. Negative regulation of IL-1 induced Mmp-13 expression was confirmed by inhibiting p38 MAPK gene expression with siRNA. Transient transfection of dominant negative forms of MKK3 and MKK6 also resulted in increased levels of Mmp-13 mRNA after IL-1 beta stimulation. Mmp-13 mRNA expression induced by TNF-alpha was decreased by JNK and ERK inhibition. Western blot and zymogram analysis indicated that Mmp-13 protein expression induced by the proinflammatory cytokines were also upregulated by inhibition of p38 MAPK. Reporter gene experiments using stable cell lines harboring 660-bp sequence of the murine Mmp-13 proximal promoter indicated that transcriptional mechanisms were at least partially involved in this negative regulation of Mmp-13 expression by p38 MAPK and upstream MKK3/6. These results suggest a negative transcriptional regulatory mechanism mediated by p38 MAPK and upstream MKK3/6 on Mmp-13 expression induced by proinflammatory cytokines in PDL fibroblasts. (c) 2005 Elsevier B.V./International Society of Matrix Biology. All rights reserved.
Keywords: MMP-13; signal transduction; collagenase; periodontal diseases; periodontal ligament fibroblasts